Beyond Social Media: Gender and Health Information Exposure in Adolescent Sexual Risk Behavior Literacy - Febry Alberto; Eva Savitri (Jurnal Promosi Kesehatan Indonesia, 2026)
Background: Sexual risk behavior literacy is essential for helping adolescents understand, evaluate, and apply sexual and reproductive health information in making safe health decisions. However, the increasing use of digital media as a health information source does not always ensure adequate literacy. This study aimed to examine factors associated with literacy in sexual risk behavior among high school students in Central Kalimantan, Indonesia, with particular attention to gender and exposure to health information.Method: : A cross-sectional study was conducted from February to March 2026 among Grade X students at a public vocational high school in Palangka Raya, Central Kalimantan, Indonesia. From a population of 451 students, 90 participants were included using proportionate stratified random sampling across 12 classes. Data were collected using a structured self-administered questionnaire covering socio-demographic characteristics, health information exposure, and sexual risk behavior literacy. Data were analyzed using IBM SPSS Statistics version 25. Result: Most respondents had poor literacy in sexual risk behaviors (74.4%), whereas 25.6% demonstrated good literacy. In the multivariable model, female students had higher adjusted odds of good literacy than male students (AOR = 4.654; 95% CI: 1.454–14.896; p = 0.010). Adolescents obtaining information from formal sources had approximately four times higher adjusted odds of good literacy than those relying primarily on social media (AOR = 4.003; 95% CI: 1.213–13.207; p = 0.023). Strengthening credible school-based and healthcare-based education, gender responsive engagement, and critical appraisal of digital information is therefore necessary.